Influence of Cold work on aging response of C17200-Beryllium Copper Alloy C17200. (2017) - Hariram, M.; Theerath, Deep; Chakravarthy, P.; Arockia kumar, R.
Abstract: Progress in materials science requires deeper understanding of the correlation of properties to internal structure and how they get altered to tailor the required properties. The paper aims to explore the variation in the mechanical properties on the degree of cold work in Beryllium copper. Hardness increased with the increase in the degree of cold working and was observed that the hardness saturated beyond 40% cold work. The samples of various percentages of cold work were subjected to ageing treatment at 330°C for one hour and the trend of hardness is explained. The microstructures revealed the evolution of precipitates during aging that attributed to increase in the hardness. Dislocation density is predicted to increase during cold work and thus improving the kinetics of precipitation. Results show a very good agreement between reported experimental observations and predictions.